2014
DOI: 10.1166/jnn.2014.8591
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Late Transition Metal Complex on Amine-Functionalized SiO2 and SBA-15 for L-Lactide Polymerization

Abstract: We report the in-situ synthesis of a late transition metal catalyst on amine-functionalized SBA-15 and amorphous silica and their ring opening polymerizations of L-lactide. Funtionalizations of SBA-15 and amorphous silica with N-[3-(trimethoxysilyl)propyl]-ethylenediamine (2NS) were carried out to in-situ synthesize late transition metal catalysts on the surface of nanoporous materials. FT-IR spectra indicates that the 1,2-dimethoxyethane ligand did not participate in the reaction when (DME)NiBr2 was immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Not only the functionalized mesoporous silica can be employed as catalysts, they can be exploited as nanoreactors for incorporation of another catalytic species such as nanoparticles, [76][77][78][79] complexes 80,81 for developing state of the art encapsulated catalysts.…”
Section: -75mentioning
confidence: 99%
“…Not only the functionalized mesoporous silica can be employed as catalysts, they can be exploited as nanoreactors for incorporation of another catalytic species such as nanoparticles, [76][77][78][79] complexes 80,81 for developing state of the art encapsulated catalysts.…”
Section: -75mentioning
confidence: 99%
“…By attaching 1-methyl-3-(3-trimethoxysilylpropyl) imidazolium chloride to the pre-calcined silica and treating the mixture with potassium tert-butoxide, a heterogeneous N-heterocyclic carbene catalyst was produced. 108 Compared with PLA generated with its homogeneous N-heterocyclic carbene counterpart, the molecular weight of PLA obtained using a supported catalyst was found to be lower, as well as the narrow molecular weight distribution. Additionally, the produced heterogeneous catalyst has slightly reduced catalytic activity than its homogeneous analog.…”
Section: Entrymentioning
confidence: 89%
“…Furthermore, it was also found that heterogeneous systems made by directly activating SiO 2 with Al (Me) 3 or Al (OiPr) 3 104 were relatively poor initiators in contrast to ligand-tethered systems. Ko et al 108 presented an instance of how late transition metals can be immobilized. N- [3-(trimethoxysilyl) propyl]-ethylenediamine was employed to functionalize the amorphous silica and mesoporous silica SBA-15, which were then used as supports.…”
Section: Entrymentioning
confidence: 99%
See 2 more Smart Citations